Pengaruh Kesadaran Wajib Pajak Dan Sanksi Perpajakan Terhadap Kepatuhan Wajib Pajak UMKM: Studi Kasus di Pasar Segar Makassar - Meilani Heni Tanga Guling; Margaretha Restu Palayukan (Akuntansi Pajak dan Kebijakan Ekonomi Digital, 2024)
The role of taxes is crucial in national development, and taxpayer compliance is a key element of tax revenue. This research aims to determine the influence of taxpayer awareness and tax sanctions on MSME taxpayer compliance at Pasar Segar Makassar. This is a quantitative study using primary data and measured with a Likert scal e. The sample size in this study consists of 51 MSME business actors at Pasar Segar Makassar, determined using the Slovin method. The data analysis technique used in this study employs SPSS version 26 software. The results indicate that taxpayer awareness and tax sanctions have a positive and significant effect on MSME taxpayer compliance.